Southeast Sulawesi Public Expenditure Analysis 2012 : Public Service Delivery Performance and Development Challenges in Bumi Haluoleo - World Bank (World Bank, Jakarta, 2017)
Southeast Sulawesi is one of Indonesia's developing provinces and over the past five years has achieved one of the country's highest growth rates. In 2010, Southeast Sulawesi's economy grew at 8.2percent the third fastest in Indonesia. The poverty rate has declined significantly in the past 10 years and the unemployment rate is one the lowest in Indonesia. Per capita expenditure in Southeast Sulawesi has increased nine-fold compared to pre decentralization rates Southeast Sulawesi's consolidated per capita expenditure now falls in the top 10 in Indonesia. However, Southeast Sulawesi is still facing a range of challenges. The Human Development Index (HDI) has continued to lag at 25th in Indonesia over the past five years. Although regional Gross Domestic Product (GDP) has grown rapidly, in real per capita terms it is still far below the national provincial average. Southeast Sulawesi' poverty rate also remains above the national average. It will be important for the high and growing rate of per capita expenditure to be matched with improvements in public financial management capacity within the local government. In the context of overcoming these challenges and capitalizing on expanding opportunities, the local governments in Southeast Sulawesi and in particular the provincial government need to work harder to make the most of its budgetary resources. The development agenda and programs must be sharpened and budget allocations must be optimized to achieve development targets, especially in the strategic sectors of education, health, infrastructure and agriculture. This report contains findings and recommendations intended to support sub national governments in Southeast Sulawesi province to enhance their public financial management performance; improve the quality of evidence based planning and budgeting; and accelerate the achievement of existing development targets.